Idella : Marjorie Rawlings' "perfect maid" - Parker, Idella (University Press of Florida, 1992)
Idella Parker's recollections of Marjorie Kinnan Rawlings are as intimate and frank as their ten years together. This long-awaited memoir, written by the black woman who was cook, housekeeper, and comfort to the famous author from 1940 to 1950, tells two stories - one of their spirited friendship, the other of race relations in rural Florida in the days before integration. Personal details - Marjorie's abandon behind the wheel of her cream-colored Oldsmobile, her boiled.